Bifurcation and Degradation of Geomaterials with Engineering Applications Proceedings of the 11th International Workshop on Bifurcation and Degradation in Geomaterials dedicated to Hans Muhlhaus, Limassol, Cyprus, 21-25 May 2017 - Papamichos, Euripides; Papanastasiou, Panos; Pasternak, Elena; Dyskin, Arcady; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book contains the scientific contributions to the 11th International Workshop on Bifurcation and Degradation in Geomaterials (IWBDG) held in Limassol-Cyprus, May 21-25, 2017. The IWBDG series have grown in size and scope, since their inception 30 years ago in Germany, covering more and wider areas of geomaterials and geomechanics research including modern trends. The papers cover a wide range of topics including advances in instabilities, localized and diffuse failure, micromechanical, multiscale phenomena, multiphysics modeling and other related topics. This volume gathers a series of manuscript by brilliant international scholars who work on modern recent advances in experimental, theoretical and numerical methods. The theoretical and applied mechanics are linked successfully with engineering applications in traditional and in emerging fields, such as geomechanics for the energy and the environment. The quality of the contributed papers has benefited from the peer review process by expert referees. This book can be used as a useful reference for research students, academics and practicing engineers who are interested in the instability and degradation problems in geomaterials, geomechanics, geotechnical engineering and other related applications.
Part I. Experimental Modeling of Instabilities Localization and Degradation -- Part II. Constitutive modeling and multi-physical coupling for localization, Instabilities and Degradation of Geomaterials -- Part III Numerical Modeling of Failure, Localized Deformation and Gravity Driven Flows -- Part 4 Soil-tool/Machine Interaction -- Part V Geomechanics for Energy, Environment and Geophysics -- Part VI Micromechanics and Multi-scale Analysis of Instabilities and Degradation -- Part VII Hans Muhlhaus Tribute.
Keywords: Engineering geology; Geotechnical engineering; Geoengineering; Geotechnical Engineering and Applied Earth Sciences